Self-Compassion Training (Mirror Talk) to Reduce Homesickness in Out-of-Province Students Studying in South Sulawesi - Wulandari, Amalia Seha; Widyastuti; Cahyaningrum, Kartika (International Journal of Science and Society, 2025)
Homesickness refers to the longing to go home, which is one of the problems faced by students who are away from home because they are too long tied to their families and the surrounding environment, especially for those who have just adapted. This study aims to determine the effect of providing Self Compassion Training (Mirror Talk) to Reduce Homesickness in Students from Outside South Sulawesi Province. Participants in this study were 12 students from outside South Sulawesi Province who experienced high levels of homesickness. This study used a quantitative experimental form with a quasi-design without a control group using follow-up. Data collection was carried out using a homesickness scale and then conducting self-compassion training (mirror talk) by adapting the self-compassion module (mirror talk). Data analysis was carried out using a descriptive test method. Furthermore, an assumption test was carried out which included a normality test and a homogeneity test. The hypothesis was tested using a paired sample t-test and Anova. The results of the study showed that there was an effect of self-compassion mirror talk training to reduce feelings of homesickness in students from outside South Sulawesi Province. The measurement results obtained showed that there was a decrease in the level of homesickness after the provision of mirror talk training.